2017
DOI: 10.12973/eu-jer.7.1.1
|View full text |Cite
|
Sign up to set email alerts
|

Using Self-Determination of Senior College Students with Disabilities to Predict Their Quality of Life One Year after Graduation

Abstract: Abstract:The purpose of this study was to assess the correlation and predictive relationship between self-determination and quality of life of college students with disabilities. Subjects were 145 senior college students recruited from northern Taiwan. Subjects' age ranged from 22 to 25 years and their disabilities varied, including visual impairments (n = 16), hearing impairments (n = 17), speech/language impairment (n = 6), physical disabilities (n = 40), specific learning disability (n = 26), emotional and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 21 publications
2
14
0
1
Order By: Relevance
“…Although the existing QoL definitions and measurements of QoL consider the environments of individuals (Verdugo et al, 2014a, 2014b), these appear to be based on community and residential populations (Chao, 2018; Claes et al, 2012; García-Villamisar et al, 2013; Hasche et al, 2010; Kilroy et al, 2014) and therefore, place less emphasis on specific environmental aspects of hospital life that individuals are exposed to. As previously mentioned, this population may present with challenging behaviour, which can cause distress on the ward.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the existing QoL definitions and measurements of QoL consider the environments of individuals (Verdugo et al, 2014a, 2014b), these appear to be based on community and residential populations (Chao, 2018; Claes et al, 2012; García-Villamisar et al, 2013; Hasche et al, 2010; Kilroy et al, 2014) and therefore, place less emphasis on specific environmental aspects of hospital life that individuals are exposed to. As previously mentioned, this population may present with challenging behaviour, which can cause distress on the ward.…”
Section: Discussionmentioning
confidence: 99%
“…One of the biggest restrictions placed on patients in the described service is their observation level, which can reduce independence and autonomy (Chao, 2018). Within this service, a patient’s observation level (for example, whether the patient is 1:1 with a staff member at all times or observed every 15 or 30 minutes) is dependent on their behavioural presentations and risk factors, including their social vulnerability.…”
Section: Discussionmentioning
confidence: 99%
“…Los estudios sobre la autodeterminación de las personas con discapacidad han cobrado interés, al haberse constatado su importancia para el logro de la calidad de vida (Chao, 2018;Morán, Gómez y Alcedo, 2019;Nota, Ferrari, Soresi y Wehmeyer, 2007;Schalock, Verdugo, Gómez y Reinders, 2016;Walker y otros, 2011). Los resultados de dichos estudios indican que bajos niveles de autodeterminación impactan negativamente en la satisfacción con la vida; a su vez, un alto grado de autodeterminación se relaciona con resultados positivos en la vida adulta, tanto en lo referente a poder establecer metas personales, como en la percepción de bienestar y la inclusión social (Di Maggio, Shogren, Wehmeyer y Nota, 2020;Wehmeyer, 2020).…”
Section: Discussionunclassified
“…Having self-determination has been proven to be succesful in improving the ability and competency of children with intelectual disability. A research by Chao (2018) found that there is a positive correlation between self-determination and individuals with intelectual disabilities. Avcioglu (2012) also conducted a smiliar program to the present research which was effective to improve students self-management skills.…”
Section: Discussionmentioning
confidence: 99%